Social signification and territory: methodological approximations (Terr@ Plural, 2012)
Starting from theoretical considerations related to the concepts of territory and social signification, this paper proposes the development a methodology that allows for the identification and comprehension of the symbolic-imaginary nature of territorial projects, as well as establishing the basis for the construction of a Hermeneutics of Territory, conceived as Dialogic Territorial Hermeneutics. The main goal of this hermeneutics will be to decipher the meanings of the territory as presented in narrations and stories from communities of the southern Patagonian region of Chile. It is believed that such narrations and stories would communicate conflicting interpretations, representing both the official thinking, which is still traditional, and the dissenting thoughts in which the emergence of non-traditional hermeneutic attitudes can be seen. The projection, development and formalization of these new interpretative attitudes will be the foundation for the proposal of an effective Dialogic Territorial Hermeneutics.